2018
DOI: 10.1016/j.jpsychires.2018.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Altered resting-state connectivity within default mode network associated with late chronotype

Abstract: Current evidence suggests late chronotype individuals have an increased risk of developing depression. However, the underlying neural mechanisms of this association are not fully understood. Forty-six healthy, right-handed individuals free of current or previous diagnosis of depression, family history of depression or sleep disorder underwent resting-state functional Magnetic Resonance Imaging (rsFMRI). Using an Independent Component Analysis (ICA) approach, the Default Mode Network (DMN) was identified based … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 76 publications
1
13
4
Order By: Relevance
“…Blautzik et al (2013) revealed that daily modulation of resting-state connectivity patterns fluctuates from highly rhythmic (DMN and sensorimotor regions) to stable (frontal-cortical areas). Only one recently published article by Horne and Norbury (2018) explored the impact of chronotype on functional connectivity in the brain. Horne et al’s study results suggest that evening-oriented participants showed reduced connectivity within the DMN network.…”
Section: Discussionmentioning
confidence: 99%
“…Blautzik et al (2013) revealed that daily modulation of resting-state connectivity patterns fluctuates from highly rhythmic (DMN and sensorimotor regions) to stable (frontal-cortical areas). Only one recently published article by Horne and Norbury (2018) explored the impact of chronotype on functional connectivity in the brain. Horne et al’s study results suggest that evening-oriented participants showed reduced connectivity within the DMN network.…”
Section: Discussionmentioning
confidence: 99%
“…Converging lines of evidence point to the precuneus as a key neural substrate for diurnal preference and chronotype. Recent resting-state FMRI studies have reported reduced precuneal functional connectivity in young adult late-type individuals as compared to morning-types [18,19] and structural MRI studies -again in younger adults -have demonstrated greater grey matter volume in the same region [28,29]. More generally, task-based FMRI studies indicate a role for the precuneus in a range of paradigms including social processing.…”
Section: Discussionmentioning
confidence: 99%
“…The functional and structural substrates of diurnal preference and chronotype are poorly understood, largely due to the paucity of studies exploring these questions. Functional Magnetic Resonance Imaging (FMRI) studies of circadian typology have reported effects of chronotype/diurnal preference on attention [10,11], language comprehension [12], inhibition [13], working memory [14], reward processing [15,16], emotional processing [17] and resting connectivity [18,19] -although see Fafrowicz [20] who reported no effect of diurnal preference on resting-state connectivity as measured by ALFF (Amplitude of Low Frequency Fluctuations -an index of total power within a predefined frequency range [20]). Interpretation of the above findings is limited due to the relatively small number of studies and, to date, lack of replication.…”
Section: Introductionmentioning
confidence: 99%
“…12,15,17 In addition, decreased connectivity within PCC was related to later chronotype. 18,19 Thirdly, many studies suggest that PCC and aMPFC are related to emotion. [20][21][22] On the one hand, PCC has been pointed out as a pivotal for arousal and awareness, 22 linking with emotion, 21 and involving in affective symptoms of obstructive sleep apnea (OSA) or insomnia disorder.…”
Section: Introductionmentioning
confidence: 99%
“…23 On the other hand, functional impaired MPFC might result in emotional deficits, 10,24 and anterior DMN was implicated in emotion regulation. 18 More importantly, the core PCC-aMPFC subsystem entangles with emotion and introspection on mental states. 11 In a recent study, disrupted FC of PCC-mPFC may contribute to affective symptoms of bipolar disorder.…”
Section: Introductionmentioning
confidence: 99%